REPRESENTASI KRITIK SOSIAL PADA FENOMENA SOCIAL JUSTICE WARRIOR (SJW) DALAM LIRIK LAGU TAFSIR MISTIK KARYA GRUP BAND THE PANTURAS - Safira, Fanny; Suryawati, I Gusti Agung Alit; Joni, I Dewa Ayu Sugiarica (E-Jurnal Medium, 2025)
The rapidly growing new ideas in line with the advancement of time do not all have positive impacts. In reality, many people misinterpret these new ideas as forms of provocation and freedom without considering the established norms and values in society, such as customs and traditions that reflect the identity of a community and its way of life. The song "Tafsir Mistik" by The Panturas presents a concept based on the songwriter's concern about the condition of Social Justice Warriors, a group disseminating new ideas about freedom and attempting to infiltrate the collective consciousness of society with Westernized culture, which is entirely irrelevant to the values inherent in community life.This study aims to elucidate the implied meaning conveyed through the lyrics of "Tafsir Mistik" by The Panturas and its correlation with the representation of social criticism intended to be portrayed. The research adopts a qualitative approach, drawing upon Stuart Hall's representation theory and Roland Barthes's semiotics theory. The findings of this study reveal that the song "Tafsir Mistik" describes a depiction of the current reality of the problems caused by the massive dissemination of provocative new ideas through social media, resulting in negatif impacts on instilling moral values in society and future generations.